DESAIN DAN IMPLEMENTASI SISTEM ADMINISTRASI PEMBAYARAN ANGSURAN PINJAMAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) PEMERINTAH DAERAH KABUPATEN MALANG - Prasetyo, Andri; N. P., Yolandari Noormannidya (DINAMIKA DOTCOM, 2013)
System Administration installment loans growing at official cooperation of the Republic of Indonesia (KPRI) Malang regency government is currently still manual and conventional as well as the packaging is not good, where the recording is done only through the cash book and use the computer just as calculators and data storage media in the absence of a program or software that computerize to support performance and minimize errors. The packaging is not good to use the manual method resulted in the frequent occurrence of errors in recording the transactions as loans, installment loans and the remaining count data processing borrower. Weaknesses in the system that are still running a conventional manual and can be overcome by the application program computerized, automated legal software but not paid to help minimize errors arising from manual and conventional systems because the entire process and results of the activities are recorded and stored on the system is used.The method used for the development of this application is to make the collection of data through interviews with government officials and members KPRI Malang regency, studying ledger entry and exit as well as evidence relating to the administration of administrative problems and also loan installments through the study of literature to seek information and theories related to the research. In addition through the method of data collection, the development of these applications created using programming language Gambas 2.0 under the license